Observations of The Millennials Behavior in The Implementation of Pancasila Values in The Digital Era - Juliana Tirza (Syntax Corporation Indonesia, 2022)
Pancasila is the nation's founders' legacy of greatness or history. The values of Pancasila will progressively erode if the legacy is not handed on to the next generation. As a result, Pancasila education is critical for the community's future, particularly for the younger members. This study aims to determine how Pancasila courses have affected the millennial generation, and how Pancasila might be implemented in daily life and national and state affairs for younger generations. This scientific work was written using a method known as a literature review. According to the findings of the research, globalization is gradually eroding the impact of scientific and technological development, Pancasila, which has an adverse effect on the millennial generation. It is anticipated that many young Indonesians would begin to forget their country's identity in this new industrial period 4.0, when all young people or millennials are obliged to compete to generate new breakthroughs and creative works.